Kompetensi Manajerial Kepala Madrasah Dalam Meningkatkan Jabatan Fungsional Guru - Rochmani; Engkus Kuswarno; Nanang Hanafiah; U. Supyan Sauri (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2021)
This research is motivated by the phenomenon of the lack of knowledge or the ability of teachers in making scientific papers, which causes obstruction of the promotion of functional positions of teachers from class IV / a to group IV / b. The approach used in this research is a qualitative approach with descriptive analysis method. The data collection technique is done through observation, interview and documentation study. The results showed that: 1) Forecasting used is a type of